Clinical efficacy and hemodynamic effects of levosimendan in cardiac surgery patients after surgery - Meiling Zhao; Yunfeng Hou; Meng Yuan; Shuang Ma; Yifeng Yue (Journal of Cardiothoracic Surgery)
Abstract Objective To investigate the therapeutic effect of levosimendan on hemodynamics in patients undergoing major cardiac surgery and presenting with acute postoperative heart failure. Methods The subjects of the study were 160 patients with severe cardiac conditions who underwent surgery and had acute heart failure. Eighty cases each were assigned to the research and control groups using a random number table. Document the general patient data for each of the two groups; compare the clinical outcomes of the two groups. The hemodynamic states of the two groups were compared both before and after therapy. 48 h after surgery, echocardiography was performed in both groups to determine cardiac function. 48 h after surgery, N-terminal pro-brain B-type natriuretic peptide (NT-Pro-BNP) levels were compared between the two groups. Results The overall effective rate was significantly higher in the research group (92.5%) compared to the control group (76.25%, P < 0.05). Post-treatment, the research group demonstrated a significant reduction in CVP (9.25 ± 2.11 cmH2O vs. 11.36 ± 3.08 cmH2O, P < 0.001), heart rate (100.30 ± 8.69 bpm vs. 105.74 ± 7.69 bpm, P < 0.001), and lactic acid levels (1.68 ± 0.59 mmol/L vs. 2.69 ± 0.55 mmol/L, P < 0.001). The research group also showed improvements in SBP (117.23 ± 8.74 mmHg vs. 113.25 ± 7.55 mmHg, P = 0.002) and urine output (4.21 ± 1.76 mL/kg/h vs. 3.65 ± 1.23 mL/kg/h, P = 0.021). Cardiac function indicators 48 h after surgery indicated a higher LVEF (55.21 ± 8.04% vs. 47.18 ± 6.60%, P < 0.001) and lower LVEDVi and LVESVi in the research group (P < 0.001 for both). NT-Pro-BNP levels were significantly lower in the research group (6010.19 ± 1208.52 pg/mL vs. 9663.21 ± 2391.34 pg/mL, P < 0.001). The incidence of complications was lower in the research group (5% vs. 22.5%, P = 0.001). Conclusion Cardiac surgery patients are prone to complications with acute heart failure after surgery. Treatment with levosimendan can significantly improve clinical efficacy and reduce complications. It can also effectively improve patients' cardiac function and promote hemodynamic stability.